2005
DOI: 10.1210/en.2004-1272
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Target Gene Regulation and Coactivator Expression in Rat Uterus after Developmental Exposure to the Ultraviolet Filter 4-Methylbenzylidene Camphor

Abstract: Because the estrogen receptor (ER) ligand type influences transactivation, it is important to obtain information on molecular actions of nonclassical ER agonists. UV filters from cosmetics represent new classes of endocrine active chemicals, including the preferential ER beta ligands 4-methylbenzylidene camphor (4-MBC) and 3-benzylidene camphor. We studied estrogen target gene expression in uterus of Long Evans rats after developmental exposure to 4-MBC (0.7, 7, 24, and 47 mg/kg x d) administered in feed to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
60
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 49 publications
0
60
0
1
Order By: Relevance
“…Epidemiological studies suggest a positive correlation between blood levels of chemicals with estrogenic activity, such as organochlorine pollutants, and breast cancer incidence among women, implying that the growing risk of contracting mammary cancer may be linked to the wide distribution of synthetic xenoestrogens (12,13,(44)(45)(46)(47). On the other hand, beneficial health effects have been attributed to the dietary intake of natural phytoestrogens in food of plant origin (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies suggest a positive correlation between blood levels of chemicals with estrogenic activity, such as organochlorine pollutants, and breast cancer incidence among women, implying that the growing risk of contracting mammary cancer may be linked to the wide distribution of synthetic xenoestrogens (12,13,(44)(45)(46)(47). On the other hand, beneficial health effects have been attributed to the dietary intake of natural phytoestrogens in food of plant origin (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…However, 18S expression increased at the 24-h time point in whole uterine tissue only. Glyceraldehyde 3-phosphate dehydrogenase and b-actin are also common housekeeping genes for quantitative RT-PCR but are known to be regulated by oestrogen (Durrer et al 2005). Therefore, as a known amount of mRNA was used in each reaction, whole uterine mRNA data were analysed without reference to a housekeeping gene to prevent skewing of data at this one time point.…”
Section: Real-time Quantitative Rt-pcr (Whole Uterus)mentioning
confidence: 99%
“…Additionally, 4MBC can be re-absorbed through the skin. Durrer et al, (2005) observed that the 4-MBC altered steady-state levels of mRNAs encoding for ER alpha, ER beta, progesterone receptor (PR), IGF-I, androgen receptor, determined by real-time RT-PCR in uterus of 12-week-old offspring. Hamann et al, (2006) observed that 4-MBC was a potent inhibitor of the pituitary-thyroid-axis due to the fact that TSH serum levels were significantly elevated and the weight of the thyroid glands that was remarkably increased.…”
Section: Introductionmentioning
confidence: 99%